Dysfunctional american dream reflected in arthur miller’s death of a salesman - Mujahidah, Ivana Nabilah Qoriroh; Wardani, Agista Nidya (JEES (Journal of English Educators Society), 2021)
The research aims to find the dysfunctional American Dreams; the causes of dysfunctional American Dreams and the effects of dysfunctional American Dreams experienced by the main character, Willy Lowman, as a representation of American society.This paper is examined by applying descriptive qualitative research paradigm which is naturally interpretative. Thus, the key instrument is the researcher herself who has the authority in managing and analyzing the data, and certainly producing meaning in the process of discussion and interpretations. Moreover, to facilitate her in collecting and identifying the data, she used supporting instrument in the form of table. This study, theoretically, applied the mimetic theory as the research approach.The researcher found that Arthur Miller uses the character of Willy Loman to represent the failure of the American Dream. Willy’s quest for the American Dream leads to his failure because throughout his life he pursues the illusion of the American Dream and not the reality of it. The unachievable part of Willy’s view of the American Dream is perfection. He has subordinated by the capitalism in which Willy belongs to the proletariat where his dream is a utopia. HIGHLIGHTS: The character of Willy Lowman represented the failure of American Dream because throughout his life he pursues the illusion of American Dream. Some misperceptions of American Dream have made Willy living in utopia and committing a suicide. The study represented that not all Americans or immigrants have the same perception of the American Dreams and not all of them can reach the dreams